2007
DOI: 10.2105/ajph.2005.084871
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Support on Mental and Behavioral Outcomes Among Adolescents With Parents With HIV/AIDS

Abstract: Objectives. We examined the associations between social support and mental and behavioral outcomes among adolescents whose parents were infected with or died of HIV/AIDS. Methods. Families (parents who were HIV infected and their adolescent children) were randomly assigned to a coping skills intervention or a standard care group. After completing the intervention, the parents and adolescents were assessed for 2 years. Results. Adolescents who had more social support providers reported significantly lower lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
55
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 24 publications
(27 reference statements)
9
55
0
6
Order By: Relevance
“…In a nationally representative sample of adolescent boys who had experienced violence (e.g., witnessed violence, physical assault, and sexual assault), positive social support following trauma reduced the risk of delinquency and violent behaviors (Maschi, Bradley, & Morgan, 2008). In contrast, research has revealed that negative social support (e.g., criticism, blaming responses) or a lack of social support immediately following trauma was associated with increased rates of adolescent depression and other negative outcomes (Bal et al, 2005;Lee et al, 2007). For example, among the most vulnerable adolescents, such as those who are HIV-affected, negative social support following trauma was significantly associated with increased rates of adolescent depression, lower self-esteem, and conduct problems (Lee et al, 2007).…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nationally representative sample of adolescent boys who had experienced violence (e.g., witnessed violence, physical assault, and sexual assault), positive social support following trauma reduced the risk of delinquency and violent behaviors (Maschi, Bradley, & Morgan, 2008). In contrast, research has revealed that negative social support (e.g., criticism, blaming responses) or a lack of social support immediately following trauma was associated with increased rates of adolescent depression and other negative outcomes (Bal et al, 2005;Lee et al, 2007). For example, among the most vulnerable adolescents, such as those who are HIV-affected, negative social support following trauma was significantly associated with increased rates of adolescent depression, lower self-esteem, and conduct problems (Lee et al, 2007).…”
Section: Social Supportmentioning
confidence: 99%
“…In contrast, research has revealed that negative social support (e.g., criticism, blaming responses) or a lack of social support immediately following trauma was associated with increased rates of adolescent depression and other negative outcomes (Bal et al, 2005;Lee et al, 2007). For example, among the most vulnerable adolescents, such as those who are HIV-affected, negative social support following trauma was significantly associated with increased rates of adolescent depression, lower self-esteem, and conduct problems (Lee et al, 2007). Loss of social support was also found to be related to higher rates of PTSD; adolescents who had recently lost someone close to them were among the most vulnerable to repeating trauma and developing PTSD (Dell'Osso, 2011b).…”
Section: Social Supportmentioning
confidence: 99%
“…Domestic violence with physical punishment experience (23)(24)31,56) Difficulties with family relationships (parents and siblings) (13,31,61) Parents and friends influence to use drugs (14,56) Low emotional support at home during childhood (15,60) Alcohol abusive parents (47,54) Parents divorce 0, 19)to de tristeza; átricos. (19) Family financial problems (38) Parents with low well-being levels (52) Bad experience of family communication (52) Parents that live with or died of HIV/Aids (60) 26.4…”
Section: Family Relatedmentioning
confidence: 99%
“…(19) Family financial problems (38) Parents with low well-being levels (52) Bad experience of family communication (52) Parents that live with or died of HIV/Aids (60) 26.4…”
Section: Family Relatedmentioning
confidence: 99%
“…6 The effect of injury to a parent on recovery from injury in children and adolescents warrants further attention. Research on parental medical illness such as HIV and cancer documents the increased risk of their children for substance abuse, risky sexual behavior, emotional distress, 12 and increased prevalence of somatic symptoms. 13 Injuries sustained by parents in combat can have a variety of psychological effects on their children.…”
mentioning
confidence: 99%